Effect of chondroitin sulphate in symptomatic knee osteoarthritis: a multicentre, randomised, double-blind, placebo-controlled study. Issue 5 (4th January 2007) - Mazières, Bernard; Hucher, Michel; Zaïm, Mohammed; Garnero, Patrick
Abstract : Objective: To evaluate the efficacy and tolerability of chondroitin sulphate (chondroitin sulphate) in knee osteoarthritis. Patients and methods: A 24-week, randomised placebo-controlled trial of chondroitin sulphate (1 g/day) in patients with symptomatic knee osteoarthritis as measured on a visual analgue scale. Pain on daily activities and Lequesne's Index were the primary efficacy criteria. Secondary outcomes included the rate of responders according to the outcome measures in rheumatoid arthritis clinical trials of the Osteoarthritis Research Society International (OMERACT-OARSI) criteria, quality of life, patient's/physician's global assessments and carry-over effect after treatment. Biochemical markers of bone (CTX-I), cartilage (CTX-II) and synovium (hyaluronic acid) metabolism were also measured. Safety was assessed by recording adverse events (AEs). Statistical analysis was performed on the inter-group differences in the intention-to-treat population. Results: 307 patients were included in the study. 28 (9%) patients discontinued the study because of lack of efficacy or AEs. At the end of treatment, the decrease in pain was −26.2 (24.9) and −19.9 (23.5) mm and improved function was −2.4 (3.4) (−25%) and −1.7 (3.3) (−17%) in the chondroitin sulphate and placebo groups, respectively (p = 0.029 and 0.109). The OMERACT-OARSI responder rate was 68% in the chondroitin sulphate and 56% in the placebo group (p = 0.03). The investigator's assessments and short form 12 (SF-12) physical component reported improvement more frequently in the chondroitin sulphate than in the placebo group (p = 0.044 and 0.021, respectively). No significant difference was observed between treatment groups for changes in biomarkers over 24 weeks. However, there was a significant difference between non-responders and responders according to the OARSI criteria for 24-week changes of CTX-I (p = 0.018) and CTX-II (p = 0.014). Tolerance was considered to be satisfactory. Conclusion: This study failed to show an efficacy of chondroitin sulphate on the two primary criteria considered together, although chondroitin sulphate was slightly more effective than placebo on pain, OMERACT-OARSI response rate, investigator's assessment and quality of life.